DIMENSIONAL ACCURACY OF DIGITAL MODELS OBTAINED BY DIRECT IMPRESSION SCANNING AND GYPSUM MODEL DIGITIZATION (Ustozlar uchun, 2026)
The rapid integration of CAD/CAM technologies into prosthetic dentistry has significantly transformed clinical and laboratory workflows. One of the most debated issues in digital prosthodontics is whether direct scanning of dental impressions can provide dimensional accuracy comparable to traditional gypsum model digitization, which is still considered the reference standard for high-precision restorations.